(untitled) (JURNAL ADMINISTRASI PUBLIK, 2020)
The purpose of this study is how the effect of organizational structure on performance in the tourism department of South Bolaang Mongondow Regency. This study uses quantitative methods, the population and sample in this study amounted to 32 samples. The instruments and data collection techniques used were questionnaires. The analysis technique used to test the hypothesis of simple correlation statistical analysis or product moment chore. Based on the results of data analysis, conclusions are drawn: 1) Organizational Structure has a positive and significant effect on performance in the tourism department of South Bolaang Mongondow Regency. This means that the better the organizational structure, the higher the performance in the tourism service; 2) Organizational Structure has a significant correlation and determination (determination) on performance in the tourism department of South Bolaang Mongondow Regency. This means that the Organizational Structure is one of the dominant determinants of tourism performance in the agency. Kata Kunci : Organization, Performance, Tourism